2006
DOI: 10.3748/wjg.v12.i21.3400
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease may not be a severe disease at presentation among Asian Indians

Abstract: NAFLD in North Indian patients is a disease of young over-weight males, most of whom are insulin resistant and they tend to have a mild histological disease at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
7
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 30 publications
(43 reference statements)
8
68
7
1
Order By: Relevance
“…NAFLD series of Madan et al 8 and Duseja et al 9 Similarly, the mean BMI too in our NAFLD patients (26.25 kg/m 2 ) was comparable to the BMI reported in earlier studies from India 3,4 and was significantly higher than that of controls. Most studies from India had reported male gender, higher BMI, insulin resistance and MS as risk factors associated with NAFLD, which was also evident in our study.…”
Section: Singh Et Al Risk Factors Associated With Non-alcoholic Fattysupporting
confidence: 88%
See 2 more Smart Citations
“…NAFLD series of Madan et al 8 and Duseja et al 9 Similarly, the mean BMI too in our NAFLD patients (26.25 kg/m 2 ) was comparable to the BMI reported in earlier studies from India 3,4 and was significantly higher than that of controls. Most studies from India had reported male gender, higher BMI, insulin resistance and MS as risk factors associated with NAFLD, which was also evident in our study.…”
Section: Singh Et Al Risk Factors Associated With Non-alcoholic Fattysupporting
confidence: 88%
“…[8][9][10] The observed differences in Indian NAFLD patients include a lower frequency of MS, 9,11 lesser degree of adiposity and histological milder disease at presentation. 8 A study that compared Indians with matched Caucasians, Hispanics, Blacks and Eastern Asians showed 2-to 3-fold increase in insulin resistance, and 2-fold increase in hepatic triglyceride content in the Indian subgroup.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…53,54,59 Data from Delhi are similar and show the prevalence of IR to be 80% in patients with NAFLD. 72 It was shown in a multiethnic trial from Italy that nonobese Indian men have a higher prevalence of IR compared with Eastern Asians, Caucasians, and Hispanics, and that this higher IR was associated with higher intrahepatic TG and serum IL-6 levels. 10 This may account for the development of NAFLD at lower BMI in Asian Indians compared with other ethnicities.…”
Section: Insulin Resistancementioning
confidence: 99%
“…53,54 Other centers from India have also reported low prevalence of DM at presentation in patients with NAFLD ranging from 4% to 10%. 4,[72][73][74] Similarly, only 15% of Chinese patients with NAFLD have diabetes at presentation. 20 Diabetes was seen in only 4.2% and 4.8% of males and 5.8% and11.6% of females with steatosis and NASH, respectively, in Korea.…”
Section: Diabetes Mellitusmentioning
confidence: 99%